The Implementation of Problem Based Learning in Improving Students Reading Comprehension Through Small Group Discussion Strategy - Stefa Lahonda; Karmila Karmila (Universitas Khairun, 2023)
The purpose of the study was to know implementation of Problem Based Learning Model through small group discussion to improve student’s Reading Comprehension. This study was conducted at SMKS Kr. Solagratia Tongkaina-Manado. The design of this study was pre-experimental with one group pre-test and post-test design. The subject in study was eleventh grade of Perhotelan class were academic year 2023/2024, which consisted of 15 students. The data collected through objective test with multiple choice. The data were analyzed by comparing the mean score of the test. The mean score of the post-test (T2) is 7.3 than those of pre-test (T1) 5.2. This heads to conclusion by implementing Problem Based Learning Model through small discussion could be improve students’ ability in Reading.